Gold Nanomaterials for Imaging-Guided Near-Infrared in vivo Cancer Therapy - Tian, Yuanyuan; Qiang, Sheng; Wang, Lianhui (Frontiers in Bioengineering and Biotechnology, 2019)
In recent years, tremendous efforts have been devoted into the fields of valuable diagnosis and anticancer treatment, such as real-time imaging, photothermal and photodynamic therapy, and drug delivery. As promising nanocarriers, gold nanomaterials have attracted widespread attention during the last two decades for cancer diagnosis and therapy due to their prominent properties. With the development of nanoscience and nanotechnology, the fascinating bio-applications of functionalized gold nanomaterials have been gradually developed from in vitro to in vivo. This mini-review emphasizes some recent advances of photothermal imaging (PTI), surface-enhanced Raman scattering (SERS) imaging, and photoacoustic imaging (PAI)-guided based on gold nanomaterials in vivo therapy in near infrared region (>800 nm). We focus on the fundamental strategies, characteristics of bio-imaging modalities involving the advantages of multiples imaging modalities for cancer treatment, and then highlight a few examples of each techniques. Finally, we discuss the perspectives and challenges in gold nanomaterial-based cancer therapy.